A state of constant prodding: live music, precarity and regulation. Issue 3 (27th May 2018) - Ballico, Christina; Carter, Dave
ABSTRACT: Live music makes a vital contribution to the cultural and creative identities of cities. In turn, the spaces in which such activity takes place contribute strongly the functioning of local music and arts scenes. However, particularly in large Australian cities, there is a tension between economic development, fuelled by an extended property bubble, and the viability of small-to-medium live music venues. This tension is compounded by community attitudes toward arts and culture as well as a range of regulatory measures which govern the spaces in which this activity takes place. This paper examines the challenges inherent with developing and sustaining of live music venues in relation to the regulatory barriers associated with doing so. This paper draws on data from two qualitative examining producer accounts of live music operation in Perth, the capital of Western Australia, and Sydney, the capital of New South Wales. Both studies focused on the regulatory frameworks, and barriers associated with being able to support local, original contemporary music activity and were prompted following the closure of several highly supportive, high profile live music venues in each location. This research came in the wake of the so-called 'lock out laws', in the entertainment district of Kings Cross and surrounding suburbs, resulting in significant local and national debate around the impact and effectiveness of such laws. This paper is contextualised within debates relating to the importance of supportive live music venues, the challenges associated with developing, supporting and maintaining such spaces in light of gentrification and urban renewal strategies. As argued, these strategies, which work to enhance the vibrancy of cities – and often position arts and culture activity as being a vital component - often displace and/ or cause tensions for the spaces in which cultural and creative activity takes place during and after such regeneration.